The Role of Chronic Stress in Normal Visceroception: Insights From an Experimental Visceral Pain Study in Healthy Volunteers - Icenhour, Adriane; Labrenz, Franziska; Roderigo, Till; Benson, Sven; Elsenbruch, Sigrid (Frontiers in Psychiatry, 2020)
Visceroception is a complex phenomenon comprising the sensation, interpretation, and integration of sensations along the gut-brain axis, including pain or defecatory urgency. Stress is considered a crucial risk factor for the development and maintenance of disorders of gut-brain signaling, which are characterized by altered visceroception. Although the broad role of stress and stress mediators in disturbed visceroception is widely acknowledged, the putative contribution of chronic stress to variations in normal visceroception remains incompletely understood. We aimed to elucidate the role of chronic stress in shaping different facets of visceroception. From a well-characterized, large sample of healthy men and women (N=180, 50% female), volunteers presenting with low (n=57) and elevated (n=61) perceived chronic stress were identified based on the validated TICS chronic stress inventory. Visceral sensitivity together with perceived and recalled intensity and defecatory urgency induced by repeated rectal distensions was experimentally assessed, and compared between low and elevated stress groups. Subgroups were compared regarding state anxiety and salivary cortisol concentrations across experimental phases and with respect to psychological measures. Finally, in the full sample and in chronic stress subgroups, a recall bias in terms of a discrepancy between the perception of experimentally-induced symptoms and their recall was tested. Participants with elevated chronic stress presented with increased state anxiety and higher cortisol concentrations throughout the experimental phases compared to the group with low chronic stress. Group differences in visceral sensitivity were not evident. The elevated stress group perceived significantly higher urgency during the stimulation phase, and recalled substantially higher feelings of urgency induced by rectal distensions, while perceived and recalled intensity were comparable between groups. Volunteers with elevated stress exhibited a recall bias in terms of a higher recall relative to mean perception of urgency, whereas no such bias was observed for the intensity of experimental visceral stimulation. Our findings in healthy men and women provide first evidence that the troublesome symptom of urgency might be particularly modifiable by chronic stress and support the relevance of memory biases in visceroception. These results may help to disentangle the impact of chronic stress on altered visceroception in disturbances of gut-brain communication.